Prevalence of burns in children 0 to 14 years admitted into Paediatric surgical ward of Murtala Muhammad Specialist hospital Kano-Nigeria - Aikawa, Hussaini Muhammad; Ibrahim, A H; Muhammad, Ummi Usman (REAL in Nursing Journal, 2022)
Background: Burns internally, means an injury due to either fire or chemical on the human. In fact burn injury is a major public health problem and leading cause of childhood mobility and mortality world Wide. About 60% of all burn patient suffers from burn of intermediate severity corresponding to less than 10% of the body surface these patients can be treated as our parents. The objectives of the study are (a) To determine the age and gender group that has the highest occurrence of burns from Jan 2019 to Jan 2020 in patient admitted into paediatric surgical ward of Murtala Muhammad Specialist Hospital Kano. (b) To Identify the possible causes of paediatric burns in Paediatric surgical ward of Murtala Muhammad Specialist hospital Kano. (c) Identify the number of children with burns from January 2019 to January 2020. Methods: A retrospective study designed and census sampling technique was used were all the patients with burns were record. Results: The study shows that children aged 2 – 5 years have the highest occurrence of burns.Also Males have the highest prevalence within these months with about 58.6% compared to females. The most common cause of domestic paediatric burns admitted in Murtala Muhammad Specialist Hospital from January 2019 – January 2020 is fire and flame burn injury.the study also revealed that 87 children ranges from 0 – 14 years admitted with cases of domestic burns during the period of the study at Murtala Muhammad Specialist Hospital Kano. Conclusion: In the research, it is seen that burns are accidents damage to skin cause by heat, flame, chemical, electricity and radiation. Risk factors of burns include: gender, age, occupation that increase exposure to fire, easy access to chemical e.t.c. therefore, proper health education should be introduced especially to mothers and caregivers who do not have knowledge of the causes and preventive measures.